Metaphor as the Model of the Culture - Kačerauskas, Tomas (Problemos, 2002)
According to Rica:ur, metaphor is the model of the literature. The author asks, could metaphor serve as a model of the culture in general? Here some pro blems emerge. How this presumption is compatible with some criticisms of the culture (Baudrillard, Šliogeris)? How can the theories of metaphor and the theories of the culture be reconciled? The author builds on Rica:ur who foregrounds the ontological and visual aspects of metaphor. Furthermore, analysing the ethical aspect of metaphor, the author invokes the work of Uvinas. The author affirms that metaphor could be a model of the culture if we pay attention to metaphor's ethical aspect which is considered to be inseparable from our general view of the world. In this way the author tries to supplement the theory of metaphor with ethical approach. Another purpose of the article is to contribute to the consolidation of the discipline of philosophical poetics
Keywords: metaphor; culture; poetical identity; ethics